Primeness in Quantales - Bergamaschi, Flaulles Boone; Santiago, Regivan Hugo Nunes; Andrade, Alexsandra Oliveira (Revista de Ciência da Computação, 2019)
In this paper we propose a new concept of primeness in quantales. It is proved that this concept coincide with classical definition in commutative quantales, but no longer valid in the noncommutative setting. Also, the notions of strong and uniform strong primeness are investigated.